2010
DOI: 10.1007/s10151-010-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

Local application of gentamicin collagen implants in the prophylaxis of surgical site infections following gastrointestinal surgery: a review of clinical experience

Abstract: BackgroundSurgical site infection (SSI) is a common type of healthcare-associated infection in gastrointestinal (GI) surgical procedures, which often has major consequences for patient recovery and increased healthcare costs due to prolonged hospital stay. This article provides an overview of the efficacy and safety of prophylactic application of resorbable gentamicin-containing collagen implants (GCI) in the prevention of SSI following high-risk GI surgical procedures.MethodNine publications were identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…The authors who reported this latter study noted that the control group in the study received a collagen placebo sponge that may have promoted wound healing and therefore obscured the effect of the gentamicin-containing sponges. Moreover, the rate of SSI (10%) in the control group in this study was lower than that generally reported in the literature for patients undergoing loop-ileostomy closure (20%-40%) [2,[24][25][26][27]. de Bruin et al concluded that prophylactic use of gentamicin/collagen sponges can reduce rates of SSI after high-risk gastrointestinal operations and can also improve wound healing after pilonidal sinus excision [2].…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…The authors who reported this latter study noted that the control group in the study received a collagen placebo sponge that may have promoted wound healing and therefore obscured the effect of the gentamicin-containing sponges. Moreover, the rate of SSI (10%) in the control group in this study was lower than that generally reported in the literature for patients undergoing loop-ileostomy closure (20%-40%) [2,[24][25][26][27]. de Bruin et al concluded that prophylactic use of gentamicin/collagen sponges can reduce rates of SSI after high-risk gastrointestinal operations and can also improve wound healing after pilonidal sinus excision [2].…”
Section: Discussioncontrasting
confidence: 52%
“…de Bruin et al conducted a systematic review of published studies assessing gentamicin/collagen sponges and SSIs in various types of gastrointestinal operations [2]. They reviewed nine individual studies of medium-to-high risk operations and divided the 246 FORMANEK ET AL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saxena et al (2009) successfully showed the generation of esophageal epithelium with survivability of esophageal epithelial cells on basement membrane matrix coated collagen scaffolds (Saxena et al 2009). Gentamicin-collagen implants are also safely and successfully used in the prophylaxis of surgical site infections after GI surgery (de Bruin et al 2010).…”
Section: Collagen Implants: Other Applicationsmentioning
confidence: 99%